2017
DOI: 10.1111/jgh.13736
|View full text |Cite
|
Sign up to set email alerts
|

The significance of glypican‐3 expression profiling in the tumor cellular origin theoretical system for hepatocellular carcinoma progression

Abstract: Glypican-3 is correlated with the clinical malignant behavior of HCC. Moreover, GPC3 phenotype changes from positive to negative during tumor cells differentiation. Meanwhile, GPC3 plays a significant role in tumor cellular origin theoretical system, which can better reflect the malignant essence of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…1 ). [ 18 22 , 26 31 , 33 35 ] Among the 14 articles, 7 literature were based on China, [ 18 , 21 , 28 30 , 33 , 35 ] 4 performed in Japan, [ 19 , 20 , 22 , 26 ] 1 in Taiwan, [ 31 ] 1 in Korea, [ 27 ] and 1 in USA. [ 34 ] All articles used the method of IHC to detect GPC3 expression in tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). [ 18 22 , 26 31 , 33 35 ] Among the 14 articles, 7 literature were based on China, [ 18 , 21 , 28 30 , 33 , 35 ] 4 performed in Japan, [ 19 , 20 , 22 , 26 ] 1 in Taiwan, [ 31 ] 1 in Korea, [ 27 ] and 1 in USA. [ 34 ] All articles used the method of IHC to detect GPC3 expression in tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies [ 18 22 , 26 29 , 33 35 ] demonstrated the relevance between GPC3 expression and OS in patients with HCC treated initially by surgical operation resection. Combined analysis from all 9 studies revealed that high GPC3 levels were significantly associated with poorer OS.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, research into cancer biology has focused on the concept of CSCs. CSCs have the ability to initiate and sustain tumor formation ( O’Brien-Ball and Biddle, 2017 ; Xue et al, 2017a ). CSCs were isolated on the basis of their expression of cell surface markers such as CD44, CD24, and CD133.…”
Section: The Functional Heterogeneity Of Pscsmentioning
confidence: 99%
“…Routine H&E staining was performed as described previously. 16 The staining results were assessed independently and blindly via two experienced pathologists under light microscope.…”
Section: Haematoxylin-eosin (Hande) Stainingmentioning
confidence: 99%